Anchoring interprofessional education in undergraduate curricula: The Heidelberg story. Issue 2 (4th March 2017) - Berger, Sarah; Goetz, Katja; Leowardi-Bauer, Christina; Schultz, Jobst-Hendrik; Szecsenyi, Joachim; Mahler, Cornelia
ABSTRACT: The ability of health professionals to collaborate effectively has significant potential impact on patient safety and quality-care outcomes, especially given the increasingly complex and dynamic clinical practice environments of today. Educators of the health professions are faced with an immediate challenge to adapt curricula and traditional teaching methods to ensure graduates are equipped with the necessary interprofessional competencies and (inter)professional values for their future practice. The World Health Organization's "Framework for action in interprofessional education (IPE) and collaborative practice" promotes IPE as a key strategy to enhance patient outcomes by preparing a "collaborative practice-ready health workforce." Logistical and attitudinal barriers can hinder integration of IPE into curricula. Lessons learned through the implementation of a planned change to establish four interprofessional seminars (team communication, medical error communication, healthcare English, and small business management) at Heidelberg University Medical Faculty, Germany, are described. A key factor in successfully anchoring IPE seminars in the undergraduate curricula was the structured approach drawing on change management concepts.